A CASE STUDY UTILIZING PODCASTING FOR EDUCATIONAL PURPOSES IN ONLINE TEACHER EDUCATION - Ridho Kurniawan (Jurnal Muara Pendidikan, 2022)
This paper presents the results of a case study conducted at a university in Indonesia, which aimed to investigate the feasibility of using student-created podcasts for online interactive formative assessment in a pre-service teacher education course. The research was conducted as part of a larger, first-year initiative that aimed to record, refine, and spread efficient and original methods of using the internet for teaching and learning. Interviews with course instructors discussions in student focus groups (FGs), and overall course assessments all point to the podcasting assignment as a means by which the instructor, and students might gain new knowledge and insight from one another. Students gained the knowledge, competence, and assurance from the experience to do further independent research into technology for pedagogical reasons. This research helps us understand what future educators need to know to be successful in classrooms where digital tools like the internet and mobile devices play a central role in both teaching and learning.